Hybrid fibre-reinforced polymer–timber thin-walled structural members. Issue 9 (July 2018) - Fernando, Dilum; Teng, JG; Gattas, Joseph; Heitzmann, Michael
The increasing interest in timber as a sustainable construction material has led to the development of a new type of structures referred to as 'hybrid fibre-reinforced polymer–timber thin-walled structures'. In these structures, thin layers of fibre-reinforced polymer are combined with timber veneers to create high-performance, lightweight and easy-to-construct structural members. This new type of structural members harnesses the orthotropic properties of both timber and fibre-reinforced polymer by appropriately orientating material fibre directions for optimal composite properties as well as efficient thin-walled cross-sectional shapes. Hybrid fibre-reinforced polymer–timber thin-walled members can be used in many applications such as load-bearing walls, roofs, floor panels and bridge decks. This article describes several novel hybrid fibre-reinforced polymer–timber structural member forms and presents results from a preliminary experimental investigation into the compressive behaviour of hybrid fibre-reinforced polymer–timber wall panels. A comparison of behaviour between a hybrid fibre-reinforced polymer–timber wall panel and a pure timber wall panel is presented to show that the hybrid fibre-reinforced polymer–timber system significantly outperforms the pure timber system in terms of both load resistance and axial strain at failure.